Impact of obesity on iron metabolism and the effect of intravenous iron supplementation in obese patients with absolute iron deficiency - Laura Tarancon-Diez; Marianela Iriarte-Gahete; Pilar Sanchez-Mingo; Mª Ángeles Muñoz-Fernandez; Maria Luisa Navarro-Gomez; Yolanda M. Pacheco; Manuel Leal (Scientific Reports)
Abstract Obesity and iron deficiency (ID) are widespread health issues, with subclinical inflammation in obesity potentially contributing to ID through unclear mechanisms. The aim of the present work was to elucidate how obesity-associated inflammation disturb iron metabolism and to investigate the effect of intravenous (IV) iron supplementation on absolute iron deficient pre-obese (BMI 25.0–29.9 kg/m2) and obese (BMI > 30 kg/m2) individuals compared to healthy weight (HW) group (BMI 18.5–24.9 kg/m2). Iron-related, hematological and inflammatory biomarkers along with erythropoietin (EPO) were studied based on body mass index (BMI) in a Spanish cohort of non-anemic participants (n = 721; 67% women; median age of 48 years [IQR: 39–57]) and in a subgroup of subjects (n = 110) with absolute ID (ferritin < 50 ng/mL) after completing an IV iron therapy. Obese group exhibited higher levels of ferritin, hemoglobin (Hb), soluble transferrin receptor (sTfR) and hepcidin compared to HW group. Elevated BMI was independently associated with increased sTfR levels. While no statistical differences were found in EPO among groups, obese showed increased levels that inversely correlated with Hb only in pre-obese and obese groups. IV iron therapy on obese participants had significant improvements on iron-related parameters and Hb levels. Notable obesity-associated disturbances in iron metabolism are described and indicate a mixed ID among both, women and men. These findings highlight the importance of tailored interventions to correctly address ID in obese population.